Non-mutagenic or genotoxic effects of medicinal aqueous extracts from the Agaricus blazei mushroom in V79 cells - Luiz, R. C. (2003)
Agaricus blazei Murill is a mushroom largely consumed due to its medicinal properties. Effects of aqueous extract from its lineage AB97/11 in 2 fruiting body development stages (closed and opened pileus) were evaluated on chinese hamster V79 cells using cytokinesis blocking micronucleus (CBMN) and comet assays. The cells were treated at 0.15% concentration of aqueous extract prepared at different temperatures: ice-cold (4°C), room temperature (21°C) and warm (60°C). The extracts were applied in mutagenicity and antimutagenicity protocols (simultaneous, pre-incubation and continuous). The results showed that the aqueous extracts of Agaricus blazei lineage AB97/11 obtained at the 3 temperatures and both development stages did not present mutagenic or antimutagenic effect in V79 cells either in CBMN or comet assay.